Disposition of Cannabidiol Metabolites in Serum and Urine from Healthy Individuals Treated with Pharmaceutical Preparations of Medical Cannabis - Ana Pilar Pérez-Acevedo; Francesco Paolo Busardò; Roberta Pacifici; Giulio Mannocchi; Massimo Gottardi; Lourdes Poyatos; Esther Papaseit; Clara Pérez-Mañá; Soraya Martin; Annagiulia Di Trana; Simona Pichini; Magí Farré (Pharmaceuticals, 2020)
The use of cannabis flowering tops with standardized amounts of active phytocannabinoids was recently authorized in several countries to treat several painful pathological conditions. The acute pharmacological effects and disposition of Δ-9-tetrahydrocannabinol (THC), cannabidiol (CBD), their acidic precursors and THC metabolites after oil and decoction administration have been already described. In this study, the disposition of CBD metabolites: 7-carboxy-cannabidiol (7-COOH-CBD), 7-hydroxycannabidiol (7-OH-CBD), 6-α-hydroxycannabidiol (6-α-OH-CBD), and 6-β-hydroxycannabidiol (6-β-OH-CBD) in the serum and urine of healthy volunteers was presented. Thirteen healthy volunteers were administered 100 mL of cannabis decoction in the first experimental session and, after 15 days of washout, 0.45 mL of oil. Serum and urine samples were collected at different time points, and the CBD metabolites were quantified by ultra-high-performance liquid chromatography–tandem mass spectrometry. The most abundant serum metabolite was 7-COOH-CBD, followed by 7-OH-CBD, 6-β-OH-CBD, and6-α-OH-CBD, after decoction and oil. Both 7-OH-CBD and the 6-α-OH-CBD showed similar pharmacokinetic properties following administration of both cannabis preparations, whereas 7-COOH and 6-α-OH-CBD displayed a significant higher bioavailability after decoction consumption. All CBD metabolites were similarly excreted after oil and decoction intake apart from 6-α-OH-CBD, which had a significantly lower excretion after oil administration. The pharmacokinetic characterization of CBD metabolites is crucial for clinical practice since the cannabis herbal preparations are increasingly used for several pathological conditions.